(untitled) (Лучшие интеллектуальные исследования, 2025)
Introduction. Car transport insurance is an important legal and economic institution that provides financial compensation for damage that may be caused to owners of road vehicles and third parties. Currently, the number of vehicles in Uzbekistan is increasing significantly, which also increases the number of road accidents. This increases the demand for the insurance sector and requires its improvement.